If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4n + -4 = -56 Reorder the terms: -4 + -4n = -56 Solving -4 + -4n = -56 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -4n = -56 + 4 Combine like terms: -4 + 4 = 0 0 + -4n = -56 + 4 -4n = -56 + 4 Combine like terms: -56 + 4 = -52 -4n = -52 Divide each side by '-4'. n = 13 Simplifying n = 13
| -3s=-135 | | -30+2x=6x+18 | | n*n+8n+2= | | 18=4(s-13) | | (x-8)(4x+2)=10x(x-8) | | 3.69+49=13.6161+7x | | 7v=-350 | | -37-8x=-11x+14 | | 9=3(t+14) | | 7x+16=2x | | 13=-4 | | 8=4(y-18) | | -7x-8=8 | | 5b=-10+6b | | 28x+11=1 | | 2y^3=0 | | 7x+5=9z-5 | | 8v=-344 | | k+-15k+7=-7 | | 5b=200 | | 6cos(x)-4=0forx | | 6*cos(x)-4=0 | | x^2+px-9=(x-1)(x+q) | | -5t+12t+9t=-16 | | 8v(8v)= | | 2x^2+10x+30= | | 3f-8=6f+10 | | 28=2(-6+x) | | 5x+mk=7k | | 2(2x+3)-4=2x+5 | | -2(r+7)=14 | | 2x^2+12x+30= |